A critical evaluation of religious syncretism among the Igbo Christians of Nigeria - Anizoba, E.C. (Acta Theologica, 2021)
Syncretism has remained a persistent issue among the Igbo-speaking Christians of Nigeria. This is observed in the double allegiance of faith among many of them who, interestingly, are devotees of both Christian and African traditional beliefs/systems. Besides the belief in ritualistic charms, many Igbo/Igbo-speaking Christians consult diviners for various reasons, including security and prosperity, causes of illness and death, ways of preserving life, as well as to discern the mind of God about one’s future and destiny. Moreover, traditional oath-taking among other African traditional religious practices is common among many Igbo Christians. This article sets out to critically examine the factors that are responsible for the persistence of religious syncretism among the Igbo Christians. The study adopts a qualitative phenomenological research design and descriptive method for data analysis. Personal interviews and library resources constitute the primary and secondary sources of data, respectively. The findings reveal that lifethreatening factors such as illness, disease, insecurity, and fear are some of the principal causes of religious syncretism among the Igbo Christians.